Otter trawling with the M/L "Josie". - Cauagas, Silverio P. (Miagao,Iloilo College of Fisheries, University of the Philippines, 1956)
This report contains my observations while on apprenticeship on otter trawling with the M/L Josie from May 15 to September 30, 1951. Within that period I had the opportunity to familiarize myself, observe and to study the various fishing grounds in the Visayan sea. There are areas where the bottom is rocky so that it would seem impracticable for otter trawling and these proved to be an obstacle to one who is not very careful and acquainted with these different aspects of the bottom regions of this particular sea. There are also places where submerged vessels and other fishing paraphernalia destroyed during the war which are not indicated in the geodetic maps that proved to be another hindrance to fishing ventures. These uncharted snags cause damage to the gear. Naturally, they give much headache to the master fisherman, especially when the entire net gets lost. This fishing boat lacks space for the crew too. In some cases, the hauling of the net when the boat is rolling and pitching oftentimes causes the falling of the net upon us after it is released from the boom. This being a limited space at the stern of this boat exposes us to the hazard of being hit or swept overboard when the net is hanging from the boom. This fishing operation for the entire five months in the Visayan sea with the M/L Josie had given me the opportunity to apply the theories I had learned from school. Guarding the operation at night is not easy especially on areas with scattered rocks and coral reefs and when visibility is very poor. These can, however, be avoided if the one guard has a good knowledge in navigation. Visayan sea is a good fishing ground for otter trawling. Its resources are limitless, rich and not fully tapped. If fully cultivated, it can easily supply the needs of the entire population around the region. But there is danger of depletion, if not immediate steps are taken to curb many illegal practices of unscrupulous fisherman who are using explosives.
Report (Undergraduate, Fish Capture) Philippine Institute of Fisheries Technology. 1951
Keywords: Fish-capture.